2020
DOI: 10.1523/jneurosci.0315-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Learning and Inference Is Impaired in the Nonclinical Continuum of Psychosis

Abstract: Our perceptions result from the brain's ability to make inferences, or predictive models, of sensory information. Recently, it has been proposed that psychotic traits may be linked to impaired predictive processes. Here, we examine the brain dynamics underlying statistical learning and inference in stable and volatile environments, in a population of healthy human individuals (N = 75; 36 males, 39 females) with a range of psychotic-like experiences. We measured prediction error responses to sound sequences wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 55 publications
5
21
0
Order By: Relevance
“…In study 1, we found a significant difference between stable and volatile mismatch responses, such that mismatch was stronger in stable than in volatile periods. This mirrored previous reports of volatility effects on mismatch signals (Todd et al, 2014;Dzafic et al, 2020). However, in our study, this was mainly due to the altered mismatch response in the biperiden group, which was particularly affected during stable mismatch.…”
Section: Biperiden and The Influence Of Environmental Volatility On Mismatch Processingsupporting
confidence: 92%
See 1 more Smart Citation
“…In study 1, we found a significant difference between stable and volatile mismatch responses, such that mismatch was stronger in stable than in volatile periods. This mirrored previous reports of volatility effects on mismatch signals (Todd et al, 2014;Dzafic et al, 2020). However, in our study, this was mainly due to the altered mismatch response in the biperiden group, which was particularly affected during stable mismatch.…”
Section: Biperiden and The Influence Of Environmental Volatility On Mismatch Processingsupporting
confidence: 92%
“…It should be noted that previous reports have presented volatility effects on mismatch processing in single-channel analyses (focusing only on Fz, (Todd et al, 2014;Dzafic et al, 2020), and that the whole-volume corrected effect presented in (Dzafic et al, 2020) did not replicate in a validation data set, suggesting that the effects of volatility on mismatch might be relatively subtle compared to the size of the mismatch effect itself.…”
Section: Biperiden and The Influence Of Environmental Volatility On Mmentioning
confidence: 80%
“…The formation of prior expectations and prediction errors is also altered along the psychosis-spectrum, as indicated by impaired mismatch negativity, a brain response to violation of sensory regularities (Farkas et al, 2015;Fitzgerald & Todd, 2020;Koshiyama et al, 2020;Michie et al, 2002;Näätänen et al, 2016;Stefanics et al, 2014), that may reflect precision-weighted prediction errors (Stefanics et al, 2018). Relatedly, nonclinical individuals reporting psychotic-like experiences demonstrate deficient learning of reguralities and inference on a sensory task, and this deficit was associated with impaired mismatch negativity (Dzafic et al, 2020). We conducted exploratory analyses to investigate the association between task performance and schizotypal traits that may facilitate hypothesis generation.…”
Section: Discussionmentioning
confidence: 99%
“…Confidence was reported on an ordinal three-point scale (1 = 'not confident', 2 = 'moderately confident', 3 = 'very confident'). For more detail regarding the task and stimulus paradigm, refer to Dzafic et al (2020). and pre-processing 2.3.1…”
Section: Experimental Designmentioning
confidence: 99%
“…A similar approach, referred to as generative embedding has been used previously (Brodersen et al, 2011), however in that paper, model optimization was done using the pooled data (both training and testing). For more detail regarding DCM fitting and parameter estimation, refer to Dzafic et al (2020).…”
Section: Feature Selection Approachmentioning
confidence: 99%